Isotopic constraints on fluid evolution and ore precipitation in a sediment-hosted Pb-Ag-Ba-Zn-Cu-Au deposit in the Capricorn Orogen, Western Australia. (September 2018) - Meadows, Holly R.; Reddy, Steven M.; Clark, Chris; Harris, Chris; Martin, Laure; White, Alistair J.R.
Abstract: The Abra Pb-Ag-Ba-Zn-Cu-Au deposit in the Capricorn Orogen, Western Australia is primarily a lead and silver resource currently estimated at 47.8 Mt (indicated and inferred) of 7.3–10.1% Pb and 18–28 gt -1 Ag, although significant Cu-Au zones are also identified. The deposit is unique within sediment-hosted Pb-Zn deposits for its low Zn content, significant Cu-Au zone and high Fe content, providing a case study where the source of fluid and ore-forming processes are contentious. The combination of whole-rock hydrogen and oxygen isotope data, in situ oxygen isotope data in quartz, and in situ sulphur isotope data of pyrite and chalcopyrite, has been used to reconstruct a complex history of overprinting, involving stages of sedimentation, diagenesis and hydrothermal activity. The host sedimentary rocks consist of detrital quartz (δ 18 O ∼11–18‰) and whole rock δ 18 O values (∼9–16‰) reflecting the combined composition of detrital and authigenic minerals, diagenetic-metamorphic exchange, chlorite and iron content. Quartz in recrystallised chemical sedimentation, quartz cementation, and quartz-barite veins at low temperatures (∼100–250 °C) involved predominantly surface and formation fluids with a wide range of fluid δ 18 O values between ∼ -5‰ and 2.6‰. Quartz in chloritized host rock with disseminated pyrite and chalcopyrite-galena veins at 250–320 °C reflect exchange with fluids(s) having a narrow range of δ 18 O values (∼5–9‰), most likely formation fluids. The fluid responsible for iron oxide, pyrite and polymetallic carbonate veins appears to be a mixture of formation and lighter surface fluids, with a range of fluid δ 18 O values (∼0.8–5.5‰). In situ sulphur isotopes are consistent with reduced seawater sulphate source in all samples, therefore it is likely that metal-rich formation fluids have interacted with reduced sulphate in the host sediments to precipitate as sulphide. Mineralisation and associated alteration at Abra has caused whole rock δ 18 O values to decrease in the deposit which may be useful as a tool for exploration in similar sediment-hosted base-metal deposits. We have shown the combination of different isotopic systems, and utilisation of in situ techniques, can constrain the sources and evolution of fluid and sulphur involved in basin formation, hydrothermal alteration and base metal mineralisation. Isotopic values can be directly related to different mineral populations within a relative temporal framework and can be used to distinguish fluids between multiple events. Highlights: In situ techniques relate isotopic values directly to mineral populations. Distinguish fluids between multiple events. O- and H-isotopes reflect rock composition, diagenesis, chlorite and iron content. Abra was formed from formation and surface fluids. Sulphur isotopes are consistent with reduced seawater sulphate source.